Molecular subtypes and clinicopathological features of breastcancer - . Irianiwati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Breast cancer is a heterogeneous disease with regard to morphological spectrum, clinical presentation and response to therapy. Based on immunohistochemistry detection of estrogen receptor, progesterone receptor, Her-2 status, proliferation rate and clusters of basal gene expression, breast cancers can be classified into luminal A, luminal B, basal-like/triple negative, and Her-2 positive. It was suggested that there was a close relationship between molecular subtypes and clinicopathological features of breast cancer, as they are very important to predict prognosis and therapeutic implications.